Next-Generation Sequencing of the Complete Huaibei Grey Donkey Mitogenome and Mitogenomic Phylogeny of the Equidae Family - Jingjing Xia; Liang Chang; Dashuang Xu; Yuqing Jia; Yuanfei Ding; Chengcheng Cao; Zhaoyu Geng; Sihua Jin (Animals, 2023)
The Huaibei grey donkey (HGD) is an endangered species and a vital native breed in Anhui Province, China. However, its complete mitogenome, phylogeny, and maternal origin remain unclear. The objectives of this study were to detect the genetic diversity of the HGD and investigate its phylogenetic relationship with other breeds to inform conservation management. The complete mitogenome of the HGD was sequenced through next-generation sequencing, and the most variable region in the mitochondrial DNA displacement-loop (D-loop) was amplified via a polymerase chain reaction (PCR). Next, we used the median-joining network (MJN) to calculate the genetic relationships among populations and the neighbor-jointing method to build a phylogenetic tree and speculate as to its origin. The results showed that the mitogenome contains 22 tRNAs, 2 rRNAs, 13 PCGs, and 1 D-loop region. Analyzing the D-loop region of the HGDs, we identified 23 polymorphic sites and 11 haplotypes. The haplotype and nucleotide diversity were 0.87000 (Hd) and 0.02115 (Pi), respectively. The MJN analysis indicated that the HGD potentially has two maternal lineages, and phylogenetic analysis indicated that the Somali lineage could be the most probable domestication center for this breed. Therefore, our mitogenome analysis highlights the high genetic diversity of the HGD, which may have originated from the Somali wild ass, as opposed to the Asian wild ass. This study will provide a useful resource for HGD conservation and breeding.